Does hormonal status influence the mood of menopausal women? - Adamiak, Aneta; Tomaszewski, Jacek; Mazur, Paweł; Skorupski, Paweł; Walaszek, Paweł; Rechberger, Tomasz; Płachta, Zenon (Menopause Review/Przegląd Menopauzalny, 2002)
Rationale for the study: The bulk of evidence exists that alterations in circulating levels of oestrogens and androgens could influence the mood in menopausal women. Moreover, the sex hormones do modulate the brain function by interacting with several neurotransmitters. The aim of the study: To assess the association if any between depression and absolute levels of DHEAS, testosterone, FSH and estradiol-17b among menopausal women. Materials and methods: The study group consisted of 50 menopausal women. Depressive mood was assessed by the means of Beck scale. Patients scored more then 11 points in Beck scale were considered as depressive. Patients that did not fulfil above criteria were regarded as without mood disorder. Serum fasting levels of DHEAS, testosterone, FSH and estradiol-17 beta were estimated using commercially available RIA kits (Orion Diagnostica). Results: The mean age of patients was 53.1±6.1 years in depressive group and 52.7±4.8 years in women without mood disturbances, (p=0.8). Body mass index was 24.7±4,7 kg/m2 in depressive group and 25.6±4.0 kg/m2, p=0.5 in nondepressive patients. Depressive patient scored in Beck scale 16.8±5.3 pts. whereas non-depressive subjects 5.8±3.0, p<0.000001. The differences in hormones levels before and after 3 months of HTZ between investigated groups were not statistically different. Conclusion. The blood levels of DHEAS, testosterone, FSH and estradiol-17b do not influence the mood in menopausal women. It seems clear that other then hormonal factors play role in the development of depression in menopausal women.